Inflammatory biomarkers of low back pain and disc degeneration: a review - Khan, Aysha N.; Jacobsen, Hayley E.; Khan, Jansher; Filippi, Christopher G.; Levine, Mitchell; Lehman, Ronald A.; Riew, K. Daniel; Lenke, Lawrence G.; Chahine, Nadeen O. (Annals of the New York Academy of Sciences, 2017)
Biomarkers are biological characteristics that can be used to indicate health or disease. This paper reviews studies on biomarkers of low back pain (LBP) in human subjects. LBP is the leading cause of disability, caused by various spine‐related disorders, including intervertebral disc degeneration, disc herniation, spinal stenosis, and facet arthritis. The focus of these studies is inflammatory mediators, because inflammation contributes to the pathogenesis of disc degeneration and associated pain mechanisms. Increasingly, studies suggest that the presence of inflammatory mediators can be measured systemically in the blood. These biomarkers may serve as novel tools for directing patient care. Currently, patient response to treatment is unpredictable with a significant rate of recurrence, and, while surgical treatments may provide anatomical correction and pain relief, they are invasive and costly. The review covers studies performed on populations with specific diagnoses and undefined origins of LBP. Since the natural history of LBP is progressive, the temporal nature of studies is categorized by duration of symptomology/disease. Related studies on changes in biomarkers with treatment are also reviewed. Ultimately, diagnostic biomarkers of LBP and spinal degeneration have the potential to shepherd an era of individualized spine medicine for personalized therapeutics in the treatment of LBP.